Anisotropic Bimetallic Core–Satellite–Poly(aniline) Nanohybrids for Detection of Autoantibodies. Issue 20 (9th September 2020) - Hwang, Eun Young; Lee, Jae Hee; Lim, Dong Woo
Abstract: Bimetallic core–satellite nanoparticles are widely exploited in surface‐enhanced Raman scattering (SERS)‐based applications due to their enhanced optical properties compared to single‐component metallic nanoparticles (MNPs). In addition, anisotropic hybrid nanostructures containing both MNPs and polymeric compartments constitute a new class of functional nanomaterials for photonic applications because they show different functionalities and physicochemical characteristics at two distinct compartments. Herein, synthesis of two kinds of anisotropic bimetallic core–satellite–poly(aniline) nanohybrids (ABCPNs) using small or polymeric ligand‐coated gold nanospheres or gold nanorods as seeds is reported. The ABCPNs exhibit enhanced optical properties due to a local electromagnetic field generated in the narrow interparticle gap between core and satellite nanoparticles. Furthermore, a SERS‐based quantitative analysis of autoantibodies against cyclic citrullinated peptide using the ABCPNs as SERS nanoprobes for a diagnosis of early rheumatoid arthritis is demonstrated, suggesting that these multifunctional nanostructures will be potential for advanced SERS‐based biosensors. Abstract : Two kinds of anisotropic bimetallic core–satellite–poly(aniline) nanohybrids are developed as surface‐enhanced Raman scattering nanoprobes to detect autoantibodies of cyclic citrullinated peptide via magnetic field‐based separation using magnetic bead.